2004
DOI: 10.1111/j.1442-200x.2004.01840.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of laboratory data to identify risk factors of giant coronary aneurysms due to Kawasaki disease

Abstract: The author's propose that a serum sodium concentration of <135 mEq/L at the patient's first visit to hospital may be a predictor of giant coronary aneurysms due to Kawasaki disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 8 publications
5
30
1
2
Order By: Relevance
“…It is known that patients with KD also frequently develop hyponatremia [4,7,10]. Our present study disclosed that the prevalence of hyponatremia is nearly one third of the patients with KD, which is in agreement with the previous reports [4,10].…”
Section: Discussionsupporting
confidence: 95%
“…It is known that patients with KD also frequently develop hyponatremia [4,7,10]. Our present study disclosed that the prevalence of hyponatremia is nearly one third of the patients with KD, which is in agreement with the previous reports [4,10].…”
Section: Discussionsupporting
confidence: 95%
“…They also cited that the syndrome of inappropriate secretion of antidiuretic hormone (SIADH) in KD has sometimes been reported, and cerebral vasculitis is thought to be the etiology of SIADH in KD. Nakamura et al [2] also recently reported that hyponatremia at the patient's first visit to hospital might be a predictor of giant coronary aneurysm (>8 mm), which was not mentioned in Watanabe et al's study. Nakamura et al speculated that the relationship between hyponatremia and giant coronary aneurysms is based on the permeability of the endothelium, severity of the illness, dehydration, duration of period with fever, and so forth [2].…”
Section: Sirsmentioning
confidence: 87%
“…The Harada score, designed to identify the severely affected individuals who need intravenous gamma-globulin (IVGG) therapy, suggests that leukocytosis more than 12,000/mm 3 , platelets less than 350,000/mm 3 , semi-quantitative CRP more than 3+, hematocrit less than 35%, albumin less than 3.5 g/dL, age less than 12 months and male gender are risk factors [7]. Fever duration prior to treatment and an initial sodium concentration of less than 135 mEq/L have also been suggested to be risk factors of CAA [8,17]. In addition, low serum albumin has been reported as a risk factor in multiple studies [8,20].…”
Section: Introductionmentioning
confidence: 95%